A Contemporary Simulation Infused in the Business Communication Curriculum: A Case Study. Issue 3 (September 2013) - Drury-Grogan, Meghann L.; Russ, Travis L.
This research examines students' reactions to a contemporary simulation infused in the business communication curriculum. Results show that students indicated the experience helped them learn how to work better as a team, how to maintain composure, how the business world works, and how to improve their communication. Students also verified the validity of the simulation, stating that it prepared them for the business world by providing them with a challenging yet positive experience to demonstrate learned business communication principles. Details about the pedagogical framework of the business communication simulation and possible explanations and implications behind the findings are discussed.